Porous Al2O3 ceramics with spontaneously formed pores and enhanced strength prepared by indirect selective laser sintering combined with reaction bonding. Issue 10 (July 2020) - Dong, Ye; Jiang, Hongyi; Chen, Annan; Yang, Ting; Zou, Tingting; Xu, Dong
Abstract: Complex-shaped porous Al2 O3 ceramics with spontaneously formed pores and enhanced strength were prepared by indirect selective laser sintering (SLS) combined with reaction bonding (RB) using Al2 O3, Al and epoxy resin E12 mixed powders as raw materials. The influence of the Al amount (0–32.5 wt%) on microstructure, dimensional change, porosity, pore size distribution and bending strength of sintered bulks were investigated. The phase transition, pore structure evolution and strength enhancement mechanisms of porous ceramics with Al addition were analyzed. Owing to distinctive characteristics of Al oxidation in the RB process, including volume expansion during oxidation, spontaneously formed pores and improved bonding force, the change rate in dimension was reduced, the porosity was maintained and bending strength was enhanced, compared with the case of adding only organic binders. The sintered bulks with the Al addition of 22.5 wt% had a dimensional change of <0.99%, porosity of 54.5 ± 0.2% and maximum bending strength of 10.8 ± 0.6 MPa, which was 6.8 times as that of samples with no Al addition. The findings illustrate that understanding pore structure evolution and strength enhancement mechanisms will help design high-performance porous Al2 O3 ceramics prepared by powder-based additive manufacturing.